Sardine and anchovy as bioindicators of metal content in Greek coastal waters - SOFOULAKI, KATERINA; KALANTZI, IOANNA; ZERI, CHRISTINA; MACHIAS, ATHANASIOS; PERGANTIS, SPIROS A.; TSAPAKIS, MANOLIS (Mediterranean Marine Science, 2022)
Metal and element concentrations (Li, Na, Mg, P, Ca, V, Mn, Fe, Co, Ni, Cu, Zn, Ga, As, Se, Rb, Sr, Mo, Pd, Cd, Cs, Ba, Hg, Tl, Pb, U) were monitored in the tissues of sardine (Sardina pilchardus) and anchovy (Engraulis encrasicolus) from six Greek coastal areas subjected to different natural and anthropogenic forcings in order to be assessed as bioindicator species of marine metal pollution. Sardine and anchovy provided a thorough view of the metal pollution load of each site in accordance with local pollution sources. The wide range of pressures applied in Elefsina Gulf and Thermaikos Gulf are depicted in the large number and the kind of elements reaching maximum concentrations among the sites (e.g. Pb, Cu, Hg, As in Elefsina Gulf, and Cd, Ni, P in Thermaikos Gulf) while in the rest of the sites (Amvrakikos Gulf, Strymonian Sea, Thracian Sea, Artemisium Straits), few elements were found at maximum levels. Statistically significant site-specific differences in metal content were detected. The differentiation in metal content of the fish tissues among the sites could be attributed to anthropogenic pressures, different background levels and environmental conditions. Sardine and anchovy can be evaluated as appropriate, reliable and useful bioindicator species of marine metal pollution.